A new Orzolina Machado, 1987, from the Canary Islands (Coleoptera: Carabidae: Bembidiinae) - Machado, Antonio (Zootaxa, 2025)
Orzolina kratkyi sp. nov. is described from the island of Tenerife, in the Canarian archipelago. This endemic genus was known before from a single species in the eastern islands, Orzolina thalassophila. Both species live similarly, on the intertidal zone and are covered by the sea at full tide. A description and images of the imago and aedeagus are provided. The new species is characterized by its smaller size, more transverse pronotum and uniformly oval elytra. The mtCOI genetic distance between both species is 12.8%.